Knowledge of Midwives as a Healthcare Provider About Hypertensive Disorders During Pregnancy - Indarti, Junita; Prasetyo, Sandy (Indonesian Socety of Obstetrics and Gynecology, 2019)
Objective: To investigate the knowledge of midwives about hypertensive disorders during pregnancy.   Methods: The study design is cross-sectional by evaluating the knowledge of midwives regarding hypertensive disorders during pregnancy by using questionnaire. This study was conducted in Jakarta during the period between September and October 2017. The subject is a midwife member of Indonesian Midwives Association (IBI) practicing in DKI Jakarta, Indonesia.   Results: Total respondents were 639 practicing midwives in Central, South, West and North Jakarta. A total of 323 (50.5%) of the respondents had a sufficient level of knowledge about the basic science of high blood pressure in pregnancy, 372 (58.2%) of respondents had a good level of knowledge related to clinical examination and early diagnosis of high blood pressure in pregnancy, and 385 (60.3%) of respondents had a good level of knowledge about the management of high blood pressure in pregnancy. The location of the clinic, physician attendance, the number of patients treated by the midwives, and the number of midwives attending the clinic had significant association with the knowledge level of the subjects (all P values < 0,05)   Conclusion: The lowest knowledge level was about the basic science of hypertensive disorders during pregnancy. Factors affecting the knowledge levels of the midwives were location of the clinic, physician attendance, the number of patients treated by the midwives, and the number of midwives attending the clinic   Keywords: knowledge, midwive, hypertensive disorders, pregnancy, preeclampsia